Causes of runner’s diarrhea and dietary recommendations to avoid it - systematic review - Jedlina, Klaudia; Pacek, Katarzyna; Makowska, Karolina; Kamińska, Izabela; Pikulicka, Agata; Szulc, Izabela; Swacha, Weronika; Piekarska, Małgorzata; Kasperski, Radosław; Rusin, Klaudia (Journal of Education, Health and Sport, 2023)
Complaints of diarrhea and other gastrointestinal symptoms are common among endurance runners. These problems may interfere with athletic activities and be the main cause of underperformance during sports events. It is estimated that this difficulty affects 30 to 90 percent of long-distance runners. The most important pathophysiological factors affecting the occurrence of gastrointestinal symptoms are ischemia and mechanical damage to the intestines, as well as the secretion of neuroendocrine substances. The diet before physical exercise is also one of the most significant factors related to the appearance of gastrointestinal symptoms. Avoiding the intake of fat, caffeine, protein, fiber, non-steroidal anti-inflammatory drugs and dehydration before performance is one of the suggestions for preventing runner’s diarrhea. There are new recommendations for athletes, such as avoidance of fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) and the intake of multiple transportable carbohydrates. It seems that a short-term gluten free diet has no effect on the performance of athletes but further research is needed. Mechanisms of runner’s diarrhea are still poorly understood, so more research needs to be conducted to improve the recommendations to runners.